2021
DOI: 10.1177/21925682211057491
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Robotic Versus Freehand Pedicle Screw Placement After One-to Three-Level Lumbar Fusion

Abstract: Study Design Retrospective cohort study Objectives The purpose of this study is to compare patient-reported outcome measures (PROMs) for patients undergoing one-to three-level lumbar fusion using robotically assisted vs freehand pedicle screw placement. Methods Patients who underwent either robotically assisted or freehand pedicle screw placement for one-to three-level lumbar fusion surgery from January 1, 2014 to August 31, 2020 at a single academic institution were identified. Propensity score matching was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Studies comparing robotic usage to other techniques are limited to adult patients, but have found that the robot performs as well as any, or superior to, other methods in regards to accuracy, patient reported outcomes, and revision rates [3–5,11,14,15 ▪ ,16]. Katsevman et al [13 ▪ ] compared robot-guided screw placement to fluoroscopy-guided and found that the robotic screws had significantly less facet joint violation.…”
Section: Comparison To Freehand Fluoroscopy-guided and Navigation Tec...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies comparing robotic usage to other techniques are limited to adult patients, but have found that the robot performs as well as any, or superior to, other methods in regards to accuracy, patient reported outcomes, and revision rates [3–5,11,14,15 ▪ ,16]. Katsevman et al [13 ▪ ] compared robot-guided screw placement to fluoroscopy-guided and found that the robotic screws had significantly less facet joint violation.…”
Section: Comparison To Freehand Fluoroscopy-guided and Navigation Tec...mentioning
confidence: 99%
“…In most cases, robot-assisted pedicle screw placement is combined with surgical navigation so the operating surgeon can visualize the instrument trajectory in all planes and double-check the preplanned screw trajectory in real time [1 ▪▪ ,2,3,5,6]. Robot use in adult spinal surgery has been well documented and demonstrates comparable, if not superior, accuracy in placement of pedicle screws when compared to freehand, fluoroscopy-guided, or other navigated techniques [3–5,7 ▪▪ ,8,9,10 ▪ ,11,12 ▪ ,13 ▪ ,14,15 ▪ ,16].…”
Section: Introductionmentioning
confidence: 99%
“…Freehand pedicle screw xation during the operation is a universal and acceptable approach; [3][4][5] but despite that, a postoperative computed tomography (CT) study demonstrated that 3.9% of screw breach for free-hand pedicle screw technology was identi ed 6 . Another similar publication demonstrated 13.5% of misplace screw 5 .…”
Section: Introductionmentioning
confidence: 99%
“… 15 Evidence that the use of robotics will lead to improved survival, function, and patient-reported outcomes and decreased complications is not consistent, and while there is some evidence of benefits over a fluoroscopic approach, many studies have shown equivalent or variable outcomes. 16 17 18 19 …”
mentioning
confidence: 99%
“…15 Evidence that the use of robotics will lead to improved survival, function, and patient-reported outcomes and decreased complications is not consistent, and while there is some evidence of benefits over a fluoroscopic approach, many studies have shown equivalent or variable outcomes. [16][17][18][19] Spine surgery costs are notoriously high, and there are already criticisms and concerns over the economic effects. 20,21 Some studies have looked at overall costs, costs of different approaches to the spine, and geographic variation in costs; [22][23][24] however, there are few studies directly evaluating costs in robotic-assisted spine surgeries compared with more manual nonrobotic techniques.…”
mentioning
confidence: 99%